2007
DOI: 10.4097/kjae.2007.53.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lidocaine Prior to Extubation Reduces Emergence Agitation and Cough in Pediatric Adenotonsillectomy under Sevoflurane Anesthesia

Abstract: Background: Sevoflurane is widely used to ambulatory pediatric anesthesia. But, sevoflurane is associated with a high incidence of emergence agitation in children. In this study, we examined the effect of single intravenous lidocaine prior to extubation on emergence agitation and cough in children undergoing adenotonsillectomy.Methods: All patients received a standardized anesthetic regimen with 2 3% sevoflurane in 50% O2/N2O after anesthetic induction with intravenous glycopyrrolate 0.004 mg/kg, thiopental 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A total of 571 records were identified through database searching and other sources, the full texts of 50 articles were examined in detail. And finally we included 12 RCTs 3 4 5 9 10 11 12 13 14 15 16 17 with a total of 1416 participants. Searching process was shown in the flowchart ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 571 records were identified through database searching and other sources, the full texts of 50 articles were examined in detail. And finally we included 12 RCTs 3 4 5 9 10 11 12 13 14 15 16 17 with a total of 1416 participants. Searching process was shown in the flowchart ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Anesthetists have been administering lidocaine intravenously or topically to prevent perioperative events during pediatric general anesthesia for many years. However, some studies have proposed that lidocaine prevents perioperative events such as cough and agitation but not laryngospasm 3 4 5 6 . Given that most studies are underpowered due to low incidence of laryngospasm or small-sized candidates, we decided to conduct a network meta-analysis of randomized controlled trials that evaluated the effect of intravenous or topical lidocaine in preventing laryngospasm during pediatric general anesthesia.…”
mentioning
confidence: 99%
“…Although intravenous infusion of lidocaine may delay recovery, postoperative sore throat is reduced, possibly lessening agitation. [7,8] The mechanism by which lidocaine relieves sore throat and cough remains unclear, but it is known that the drug reduces secretion of neuropeptides in the brainstem and airway by inhibiting stimulation of sensory C fibers in the airway and reducing stimulation of the mucosa in the airway by the tracheal tube. [26] One study found that lidocaine reduced agitation by lessening airway stimulation [8] and another found that the drug had no effect on agitation.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] The mechanism by which lidocaine relieves sore throat and cough remains unclear, but it is known that the drug reduces secretion of neuropeptides in the brainstem and airway by inhibiting stimulation of sensory C fibers in the airway and reducing stimulation of the mucosa in the airway by the tracheal tube. [26] One study found that lidocaine reduced agitation by lessening airway stimulation [8] and another found that the drug had no effect on agitation. [27] In the former study, 1 mg/kg of 1% lidocaine or 2 mg/kg of 2% lidocaine was administered after return of spontaneous breathing; in the latter study, lidocaine 1.5 mg/kg was administered at the end of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation